Proper Bacillus Calmette-Guérin (BCG) Scar Formation and Administration in Children under 2 years in a Tertiary Care Hospital - Khan, Sher Afghan (International Journal of Pathology, 2022)
Background: Bacillus Calmette-Guérin (BCG) vaccine is considered to be one of the most crucial vaccines for the immunity of Tuberculosis (TB) in the pandemic and endemic areas. Dose is administered to the children under 5 years of age in the right deltoid area of the arm. It has been determined that the number of individuals who have scar formation are less susceptible to infections and diseases in their later life. In Pakistan there is a lack of data that determines the proper administration of the BCG vaccine with scar formation.Methodology: A cross sectional study was conducted at Railway General Hospital, Rawalpindi for a period of 6 months from December 2019 to March 2020. Total number of 359 infants, less than 4 years of age were included in the study. Location and presence of BCG scar was noted and different questions regarding the Knowledge of the BCG vaccine administration, knowledge of mother regarding the BCG vaccine, her education and the scar site were included.Results: Out of 359 infants, 90 percent (323 individuals) of the mothers had the information that they had to administer the injection. Among these 359 infants scar was found to be in around 78 percent (--280) of infants at the correct right deltoid muscle of the arm, whereas the remaining 22 percent (79 infants) had no scar or the scar formation was not in the right deltoid area, it was either in the right triceps or biceps of the body. Among these 22 percent infants the dose was found to be administered in biceps of 76 percent (--60) infants, in triceps around 9 (--7) percent and in the remaining 15 percent (--12) there was no scar formation.Conclusion: Our finding suggests that most of the mothers are aware of BCG vaccination and the BCG is present and at the correct site for most children, however quite a few being unaware and having an improper or no scar raises a concern.